STRATEGI PONDOK PESANTREN AS-SALAM TURIDE KOTA MATARAM DALAM PENINGKATAN PARTISIPASI MASYARAKAT DI BIDANG KEAGAMAAN - Siti Almayani; Zaenudin Amrulloh (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This study aims to determine the strategy of  As-Salam Turide Islamic Boarding School Lendang Lekong in increasing community participation in the religious activity. The type of research used in this research is qualitative research by conducting field research. Sources of data obtained primary and secondary. Data collection techniques used are observation, interviews, and documentation. Data analysis used descriptive qualitative analysis. Through the research conducted, it was found that the strategy of the As-Salaam Turide Lendang Lekong Islamic Boarding School in increasing community participation starting from the majlis taklim activity, the community was very enthusiastic about participating in the recitation held every Saturday. This activity was attended by children, parents and fathers. The activity of praying in congregation is a pillar of the Islamic religion that must always be maintained. Prayers are not only for students but also for children, and the people of this village who participate in congregational prayers. The activity of reading the Al-Quran in congregation has a good impact on the Lendang Lekong environment